2003
DOI: 10.1128/jvi.77.13.7393-7400.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Virus-Encoded Chemokine vMIP-II Inhibits Virus-Induced Tc1-Driven Inflammation

Abstract: The human herpesvirus 8-encoded protein vMIP-II is a potent in vitro antagonist of many chemokine receptors believed to be associated with attraction of T cells with a type 1 cytokine profile. For the present report we have studied the in vivo potential of this viral chemokine antagonist to inhibit virus-induced T-cell-mediated inflammation. This was done by use of the well-established model system murine lymphocytic choriomeningitis virus infection. Mice were infected in the footpad, and the induced CD8؉ T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…Confirming recent analysis (Frigerio et al, 2002;Lindow et al, 2003;Madsen et al, 2003), both CXCL10 and CCL3 acted as chemoattractants of splenocytes from LCMV-infected WT mice, and flow cytometric analysis revealed that the recruited cells were activated CD8 ϩ T-cells and cells with a low-angle/side scatter pattern consistent with that of mononuclear phagocytes, the two cell types known to dominate in the virus-induced inflammatory exudate (Ceredig et al, 1987;Christensen et al, 1995) (data not shown). In contrast, CCL3, but not CXCL10, induced the migration of cells from LCMV-infected CXCR3-deficient mice.…”
Section: Cxcr3 Expression On Primed Cd8 ؉ T-cellssupporting
confidence: 50%
See 4 more Smart Citations
“…Confirming recent analysis (Frigerio et al, 2002;Lindow et al, 2003;Madsen et al, 2003), both CXCL10 and CCL3 acted as chemoattractants of splenocytes from LCMV-infected WT mice, and flow cytometric analysis revealed that the recruited cells were activated CD8 ϩ T-cells and cells with a low-angle/side scatter pattern consistent with that of mononuclear phagocytes, the two cell types known to dominate in the virus-induced inflammatory exudate (Ceredig et al, 1987;Christensen et al, 1995) (data not shown). In contrast, CCL3, but not CXCL10, induced the migration of cells from LCMV-infected CXCR3-deficient mice.…”
Section: Cxcr3 Expression On Primed Cd8 ؉ T-cellssupporting
confidence: 50%
“…Third, mRNA levels for CXCL10 are rapidly upregulated in virus-infected organs, including the CNS (Asensio et al, 1999;Nansen et al, 2000). Fourth, in vitro CXCL10 functions as a chemoattractant of relevant effector cells (i.e., activated CD8 ϩ T-cells and monocyte/macrophages) (Frigerio et al, 2002;Lindow et al, 2003), and this requires expression of CXCR3 (present study). Most important, mice deficient in CXCR3 expression infected intracerebrally with LCMV are relatively resistant to the virus-induced CD8 ϩ T-cell-mediated meningitis, which invariably kills similarly infected WT mice (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations